PENGARUH STRES KERJA DAN MOTIVASI KERJA TERHADAP KUALITAS KEHIDUPAN KERJA PERAWAT DI RSUD KOTA SALATIGA - Saptita, Azzahra Putri; Maghfur, Sya'ban (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2025)
This study aims to examine the influence of job stress and work motivation on the quality of work life (QWL) among nurses at Salatiga City General Hospital. QWL is a critical factor in fostering a productive and supportive work environment for healthcare professionals. This research employs a quantitative approach with an explanatory survey method. A total of 158 nurses were selected through simple random sampling. Data were collected using a Likert- scale questionnaire measuring three main variables: job stress, work motivation, and quality of work life. The multiple regression analysis revealed that job stress has a significant negative effect on QWL, while work motivation has a significant positive effect. Simultaneously, both variables significantly influence nurses’ quality of work life. These findings highlight the importance of stress management and motivation enhancement strategies in improving nurses’ well-being and the overall quality of healthcare services.